2011
DOI: 10.1186/1756-9966-30-42
|View full text |Cite
|
Sign up to set email alerts
|

Promising cytotoxic activity profile of fermented wheat germ extract (Avemar®) in human cancer cell lines

Abstract: Fermented wheat germ extract (FWGE) is currently used as nutrition supplement for cancer patients. Limited recent data suggest antiproliferative, antimetastatic and immunological effects which were at least in part exerted by two quinones, 2-methoxy benzoquinone and 2,6-dimethoxybenzquinone as ingredients of FWGE. These activity data prompted us to further evaluate the in vitro antiproliferative activity of FWGE alone or in combination with the commonly used cytotoxic drugs 5-FU, oxaliplatin or irinotecan in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 18 publications
4
57
0
Order By: Relevance
“…Our findings, related to FWGE activity in OVCA, are consistent with those of Mueller et al 7 , who demonstrated FWGE activity against a single ovarian cancer cell line, A2780. Our data demonstrated that A2780 (and Chi) exhibits the highest levels of FWGE sensitivity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings, related to FWGE activity in OVCA, are consistent with those of Mueller et al 7 , who demonstrated FWGE activity against a single ovarian cancer cell line, A2780. Our data demonstrated that A2780 (and Chi) exhibits the highest levels of FWGE sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…6 FWGE has been evaluated in vitro and shown to induce apoptosis in many cancer cell types, including leukemia, melanoma, breast, colon, testicular, head and neck, cervical, ovarian, gastric, thyroid, and brain carcinomas. 7–9 Observations from human clinical trials suggest beneficial effects of FWGE on disease progression and survival in patients with melanoma 10 and colorectal cancer. 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Avemar was reported to be an effective adjuvant agent in cancer treatment for several types of cancer. such as breast, colon, lung and prostate cancer (11). However, the mechanism of the anti-angiogenic effect of Avemar is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated cytotoxic effects of Avemar on nearly all types of cancers that's why we did not do any cell viability in this project. Therefore, the Avemar concentrations were determined according to the literature (11)(12)(13)(14). The main aim of the present study was to determine the effects of Avemar on angiogenesis.…”
Section: Introductionmentioning
confidence: 99%